Strains of a virtuoso: pacemaker infection and ventricular tachycardia in a violinist - Yuanguo Chen; Haibo Zhang; Qi Qiao; Lian Ma (BMC Cardiovascular Disorders)
Abstract Purpose Pacemaker-related infections are serious complications of cardiac implantable electronic devices (CIEDs). This case report aims to describe the occurrence of pacemaker pocket infection and recurrent ventricular tachycardia (VT) in a Chinese amateur violinist with sick sinus syndrome (SSS), and to explore the possible connection between occupational habits and the infection, as well as VT. Methods A 76-year-old male violinist with a Biotronik Evia DR dual-chamber pacemaker presented with syncope and signs of a pacemaker pocket infection three years after implantation. Despite initial antibiotic treatment, the infection persisted with slightly elevated C-reactive protein (CRP) and negative cultures. The VT originated from the right ventricular outflow tract (RVOT), as confirmed by echocardiography and ECG findings. The infection was treated with debridement and extraction of the pacemaker and leads. Results Debridement and extraction of the pacemaker and leads successfully resolved both the VT and the infection. The VT was likely linked to the infected lead, while the pacemaker infection was attributed to the patient’s violin playing, which caused mechanical stress and skin damage at the pacemaker site. Postoperative recovery was uneventful, with no recurrence of infection or arrhythmias at follow-up. Conclusion This case highlights the importance of considering a patient’s occupational habits when selecting pacemaker pocket sites to prevent infections and complications. In this case, the patient’s violin playing likely contributed to mechanical stress at the pacemaker site, leading to infection. Early identification and appropriate management, including device removal, are crucial to prevent further complications.